Semen quality characteristics of White Pekin, Kuttanad (Anas platyrhynchos domesticus) and Muscovy (Cairina moschata momelanotus) drakes - CYRIAC, STELLA; JOSEPH, LEO; A, PEETHAMBARAN P; K, NARAYANANKUTTY; K, KARTHIAYINI (The Indian Journal of Animal Sciences, 2013)
An experiment was conducted in drakes of Kuttanad, White Pekin and Muscovy breeds to study the macroscopic and microscopic parameters of semen quality. Manual massage method was used for the collection of semen. There was no significant difference in the semen volume between the breeds and also between the drakes within breeds. Majority of the semen samples were white and the appearance score was similar in the 3 breeds. Semen pH was slightly alkaline in all the breeds. The density of spermatozoa differed significantly between the breeds with a significantly lower value in Muscovy drakes. The percentage of live, dead, normal and abnormal sperms did not differ significantly between breeds and also between drakes of the same breed. Methylene blue reduction time (MBRT) was higher in Muscovy when compared to White Pekin and Kuttanad. But, MBRT showed no significant difference when estimated using 2 different extenders, viz. lake poultry semen extender (LPSE) and Beltsville poultry semen extender (BPSE) in White Pekin and Muscovy. The spermatozoa of the 3 breeds were able to withstand heat shock for 10 min and cold shock for up to 1 h.